1
$\begingroup$

Let $\psi(z)$ denote the Digamma function, $\psi(z)=\frac{d}{dz}\ln \Gamma(z)=\frac{\Gamma'(z)}{\Gamma(z)}$. I am meant to show the following properties of $\psi$:

  1. $\psi$ is meromorphic in $\mathbb{C}\backslash\{0,-1,-2,-3,...\}$
  2. $\psi(1)$=$-\gamma$ where $\gamma$ is the euler mascheroni constant.
  3. $\psi(z)=-\gamma-\frac{1}{z}-\sum\limits_{\nu=1}^\infty \left(\frac{1}{z+\nu}-\frac{1}{\nu}\right)$

So far I am quite stuck on what to do. I know about the completion formula, stirling's formula, and the duplication formula but none of those appear to apply. I cannot find a way to characterize $\Gamma'(z)$ either. Any tips, hints, or suggestions would be much appreciated!

$\endgroup$
2
$\begingroup$

Hints/guidelines:

$1$. Prove that $\Gamma(z)$ has no zeroes so $\psi(z)$ can have no singular points other than the poles $0,-1,-2,...$. Then it's not too hard to prove using the properties of $\Gamma$ function that $\psi$ has the representation $$ \psi(z)=-\frac{1}{z+n}+\mathcal{E}(z+n) $$ Here $\mathcal{E}(z+n)$ is the regular part of $\psi(z)$.

$2$. See the comment.

$3.$ Non-detailed proof:

Using the definition $\Gamma'(z)$ and by replacing the $\text{log}(t)$ term with the integral $$ \text{log}(t)= \int_0^{\infty}\frac{e^{-x}-e^{-xt}}{x}, dx $$ we can show that $$ \Gamma'(z)=\int_0^\infty \frac{dx}{x}\left[ e^{-x}\Gamma(z)-\int_0^\infty e^{-t(x+1)}t^{z-1} dt \right]. $$ Using the substitution $u=t(x+1)$ we get $$ \psi(z)=\int_0^\infty\left[e^{-x}-\frac{1}{(x+1)^{z}} \right]\frac{dx}{x}. $$ Using this we can find $$ \psi(z)=\lim_{\epsilon \to 0} \left[ \int_\epsilon^\infty \frac{e^{-x}}{x}dx-\int_\epsilon^\infty \frac{1}{(x+1)^{z}x} dx \right]. $$ Substituting $1+x = e^u$ for the last integral we get $$ \psi(z)=\lim_{\epsilon \to 0} \left[ \int_{log(1+\epsilon)}^\infty \left( \frac{e^{-u}}{u}-\frac{e^{-uz}}{1-e^{-u}}\right)du -\int_{log(1+\epsilon)}^\epsilon \frac{e^{-u}}{u} du \right]. $$ Here the last integral goes to $0$ as $\epsilon \to 0$ so we get $$ \psi(z)= \int_{0}^\infty \left( \frac{e^{-u}}{u}-\frac{e^{-uz}}{1-e^{-u}}\right)du. $$ Plugging in $z=1$, subtracting the result and using substitution $x=e^{-u}$ we finally get $$ \psi(z)=-\gamma+\int_0^{1}\frac{1-x^{z-1}}{1-x}dx. $$ Now the claim follows by using $(1-x)^{-1}=\sum_{n=0}^{\infty} x^n$ and integrating term by term.

$\endgroup$
  • $\begingroup$ This was hard to follow but it definitely works, thanks. $\endgroup$ – Tony S.F. Mar 2 '16 at 16:51
  • 1
    $\begingroup$ @TonyS.F. Well I didnt add the details on purpose so you can try to fill in the blank spots and yeah there is a lot to fill. :) $\endgroup$ – Harto Saarinen Mar 2 '16 at 17:38

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.